HUBUNGAN SISTEM SETTING DENGAN LIVABILITAS RUANG TERBUKA PUBLIK MELALUI PENDEKATAN PERSEPSIPENGGUNA DI LAPANGAN PUPUTAN BADUNG – DENPASAR (BALI) - DHARMA, I MADE KRISNA ADHI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
User activity in public open space is affected by the system settings are available as well as in Puputan. Comfort of activities as one of the determining factors of livability influenced by the availability of means of support activities are also part of the setting. Conditions system settings and livability that are less good will give affect each other. The existence of such conditions makes users are likely to give a perception of poor ratings also to public open space. This study discusses the relationship of system settings with lvability of users through the perception users approach in public open space Puputan Denpasar. The study aims to determine the form of their relationship, including the condition as well as evaluating the perception of both. The method used is qualitative and quantitative rationalistic approach. Techniques analysis using place-centered map, gradation livabilitys map and perception questionnaire. To determine the condition of the system settings and livability used qualitative methods by observation, place-centered mapp used to see the dots activity that occupies a space based on a period of time, the gradation livability map is used to determine the fluctuation of livability user activity, whereas questionnaire perception method used to see the shape user perception of the system settings and livability that can later be used to show the relationship between them through correlation analysis tool SPSS. The conclusion from this study is that there is a strong and significant relationship between system settings with livability. Of the major elements forming the system settings that can enhance the activity of as forming livability comfort, so the recommendations provided are directed to the availability and arrangement of the main elements of the system settings to be distributed in the area, so that the activities that occur can be evenly and last longer while increasing condition livability public open space in Puputan.